APPLICATION AS A STEPPER MOTOR DRIVING FORCE ON THE LADDER WALKING - Heru Wardono; Indrianto. Skom. MT Indrianto. Skom. MT (Jurnal Sistem Komputer, 2005)
Series of "Application For Power Drive stepper motor Staircase Walk On" which iscontrolled by a PC this is one of the efficient use of PC applications that can manageother peripherals.In Combination the 8255 PPI is controlled by a PC was applied to describe anexample of computerization with particular reference to give a value. Addresses areunique on the PC, meaning that each one addresses only owned by a location.